Apparent mineralocorticoid excess: A diagnosis beyond classical causes of severe hypertension in a child. Issue 3 (17th January 2022) - Gulhan, Bora; Ünsal, Yağmur; Baltu, Demet; Çelik Ertaş, Nur Berna; Özdemir, Gülşah; Utine, Eda; Ozcan, H. Nursun; Duzova, Ali; Gönç, Nazli
Abstract : A genetic defect of 11 β-hydroxysteroid dehydrogenase causes apparent mineralocorticoid excess syndrome. Since 50 days of life, our patient was hospitalized several times for various reasons including hypokalemia. At the age of 3.3 years, she was diagnosed with severe hypertension (160/120 mmHg). She also had left ventricular hypertrophy and hypertensive retinopathy and referred to our center. Her renal function and electrolytes were normal except for hypokalemia. She was on captopril treatment; nifedipine and propranolol were added. Plasma renin and aldosterone concentrations were 1.13 pg/ml (1–8.2 pg/ml) and 12.2 ng/dl (35–300 ng/dl), respectively. Severe hypertension, hypokalemia, low renin and aldosterone levels pointed to the diagnosis of apparent mineralocorticoid excess syndrome. Strict salt-restricted diet and potassium citrate were ordered. Genetic analysis of the HSD11B2 gene showed c.623G>A (p.Arg208His). Spironolactone was initiated. On follow-up, amiloride was added and her blood pressure was controlled. In patients with severe HSD11B2 mutation, combination therapy of spironolactone with amiloride could be effective in controlling blood pressure.